Review Essay: Human Rights in the ’War on Terror’ - Costi, Alberto (Victoria University of Wellington Law Review, 2006)
This article is a book review of Richard Ashby Wilson (ed) Human Rights in the ’War on Terror’ (Cambridge University Press, Cambridge, 2005) (347 pages). In recent years, terrorism has metamorphosed the global security environment. States have been forced to redefine the nature of terrorism and to reassess the political, military and legal means necessary to protect the State, its institutions and its citizens. Costi states that this book places itself squarely within some of the main current debates surrounding the war on terror in which some of the contributors have been very much involved. The book advances four propositions: it challenges the view that terrorism is a novel problem requiring exceptional solutions, it shows the limits of unilateralism in globally managing the war on terror, it highlights the impact of the war on terror on human rights domestically and the potential use of an agenda of security over liberty by governments wishing to control their citizens ever more tightly, and it calls for an examination of terrorism in context. Costi concludes that the book will make readers think and perhaps inspire them to tackle terrorism without betraying the fundamental values that are the fabric of democratic societies.